Design and optimization of elastic optical networks - Trota, Tiago Ferreira Grade Dinis (2014)
The traffic volume in backbone optical networks has increased in the last few years and it is expected to continue to exhibit a high growth, with bandwidth-hungry services being the key drivers of this growth. Furthermore, the tra c is becoming more dynamic, being characterized by a strong heterogeneity. Thus, in order to cope with these changes, optical transport networks are developing towards the operation with mixed-line rates and the elastic usage of spectrum through exible frequency grids. Regarding this paradigm shift, telecommunication network operators seek to assess solutions that enable transport networks to provide capacity enhancement and scalability. However, due to the reduction in pro t margins, another parameter taken into account is the network cost, either investment or operational. Therefore, planning and optimization tools arise as valuable instruments to exploit the features of next generation optical networks, and quantify their cost-e ciency impact. The aim of this dissertation is to study the problem of optical network design. For this purpose, an optimization algorithm was developed where the objective function minimizes the network deployment cost. This algorithm allows the use of di erent terminal equipments with di erent line rates and comprises features such as regenerator placement, multi-hop grooming, inverse-multiplexing and spectrum assignment with low granularity. Moreover, in order to improve the algorithm e ciency, a multi-thread approach was used to fully take advantage of computational resources of current platforms. The algorithm was applied and examined under di erent tra c and network topology sets. The design outcomes allow us to study the trade-o between equipment prices. Also, allow to understand the importance of each of the previously mentioned features in each of the proposed sets. The computational outcomes obtained show gains in multi-thread approach, particularly when a mechanism that lets sharing information between all threads is implemented